Effects of Parents’ Smartphone Use on Children’s Emotions, Behavior, and Subjective Well-Being - Matea Bodrožić Selak; Marina Merkaš; Ana Žulec Ivanković (European Journal of Investigation in Health, Psychology and Education)
This study aimed to examine the associations between parents’ smartphone use during conversations with children, children’s emotional and behavioral reactions to parents’ smartphone use, and children’s well-being. This study was conducted on a sample of 284 children (aged 10 to 15 years, with a mean age of 12.23 in 2021; 40.2% boys). The data come from a four-wave longitudinal study (2021–2023) within the project D.E.C.I.D.E. Children reported how often their parents use smartphones during conversations with them (second wave), their emotions and behaviors related to parents’ smartphone use (third wave), and their subjective well-being (fourth wave). A proposed model was tested in which the frequency of parents’ smartphone use during parent–child conversations was a predictor, different children’s emotional and behavioral reactions to parents’ smartphone use were mediators, and children’s well-being was the criterion. The results showed that more frequent parents’ smartphone use is associated with more frequent children’s experiences of anger and sadness in situations when parents use smartphones while with children, which is linked to lower children’s well-being. More frequent parents’ smartphone use is associated with more giving up on seeking parents’ attention among children, which is related to lower well-being.